2009
DOI: 10.1007/s00414-009-0387-y
|View full text |Cite
|
Sign up to set email alerts
|

X chromosomal recombination—a family study analysing 39 STR markers in German three-generation pedigrees

Abstract: Typing of polymorphisms on the human chromosome X (ChrX) has become a standard technique in forensic genetics, and a growing number of short tandem repeats (STRs) has been established. Knowledge of marker recombination is of great significance especially when ChrX typing is used in forensic kinship testing. It is known that meiotic recombination is not a simple function of physical distance but crossing over events tend to be clustered. Information on genetic distances between markers can be gathered by family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 34 publications
5
15
1
Order By: Relevance
“…Significant linkage between HPRTB and DXS8377 is observed with a maximum LOD score of 2.959. This result is not in agreement with the results by Hering et al , where linkage complete independent segregation between HPRTB and DXS8377 was shown.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Significant linkage between HPRTB and DXS8377 is observed with a maximum LOD score of 2.959. This result is not in agreement with the results by Hering et al , where linkage complete independent segregation between HPRTB and DXS8377 was shown.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar results are obtained within the region from DXS6807 (4.74 Mb) to DXS9902 (15.32 Mb). The pattern of linked marker groups is similar to that reported by Hering et al . Significant linkage marker pairs also can be observed within the block from DXS7424 (100.61 Mb) to GATA31E08 (140.23 Mb) with the exception of combinations of DXS7133/DXS6854 and DXS7133/HPRTB.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…All intra-group genetic distances were reported to be well below 1 cM. In order to validate these figures, and to facilitate reliable use of X-STRs in practical kinship analysis, we choose to expand the existing German family data [15] into an international collaborative study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two studies [13,14] strongly suggested that our abovementioned rough and preliminary estimates of the recombination fractions between the Argus X-8 markers needed to be modified. This led us to publish the recombination pattern of 39 X-STRs as observed in German three-generation families, comprising a total of 135 meioses [15]. However, since the accuracy of the recombination fraction estimates ensuing from such analyses is critically dependent upon the number of meioses studied, we choose to expand upon the aforementioned German study.…”
Section: Introductionmentioning
confidence: 99%